Studies on Essential Oil Extracted from Hippocratae Velutina Leaves in Relation to Chemical Composition, Antioxidant and Antimicrobial Activities - Ogwuche, Christiana Ene; Tomilola, Aina; Bawa Hamza (Malaysian Journal of Science, 2025)
Plants and their constituents have been used as medicines for so many centuries. Hippocratae velutina essential oil was analyzed to determine its chemical content, antioxidant activity and antibacterial activity. H. velutina was found to contain 0.3% essential oil. By using gas chromatography, one hundred and ninety-five (195) components were discovered to have fourteen major components, with terpenes, making up 75.36% of those components. Beta ocimene has 26.16%; Farnesene, 14.60%; and others (9%), n-alkanes (7.15%), fatty acid-derived substances (6.87%), green leaf volatiles (2.35%), and Shikimate metabolites (9%). With an IC50 of 7.14±1.45 mg/ml, which is significantly lower than those of the two standards employed, H. velutina’s aerial parts demonstrated outstanding free radical scavenging activity outcome with DPPH. With MIC values between 0.15 and 0.23 mg/ml for eight out of all ten microorganisms examined, the essential oils of H. velutina leaves demonstrated antibacterial activity against selected strains of Gram-negative and Gram-positive bacteria as well as antifungal activities, with a range in the sensitivity of the microorganisms to the oil. According to the findings, the extracted oil from H. velutina has bioactive antioxidant phytochemicals capable of inhibiting a wide range of microbial growth. This confirms its use as a folkloric drug against several ailments.